1988
DOI: 10.1093/ajcp/90.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Micrometastases in the Bone Marrow, Histopathologic Features of the Primary Tumor in Breast Cancer and Prognosis

Abstract: The pathologic features of the primary tumors in 285 patients with breast cancer at the time of initial presentation, and with no clinical evidence of distant metastases, have been analyzed. The results have been compared with the detection of tumor cells in the bone marrow by use of an immunocytochemical method using antisera raised against the epithelial membrane antigen (EMA). The authors found EMA-positive cells (i.e., tumor cells) in the bone marrow of 77 (27%) patients and a significant association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 0 publications
1
41
0
1
Order By: Relevance
“…Unspecific, false-positive staining has been reported with anti-EMA as well as anti-cytokeratin antibodies (Heyderman & McCartney, 1985;Ellis et al, 1989). This underlines the importance of using both immunocytochemical as well as morphological criteria before classifying cells as tumour cells (Berger et al, 1988). There are reports that anti-cytokeratin antibodies are less sensitive in recognising breast cancer metastases than anti-EMA (Thor et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Unspecific, false-positive staining has been reported with anti-EMA as well as anti-cytokeratin antibodies (Heyderman & McCartney, 1985;Ellis et al, 1989). This underlines the importance of using both immunocytochemical as well as morphological criteria before classifying cells as tumour cells (Berger et al, 1988). There are reports that anti-cytokeratin antibodies are less sensitive in recognising breast cancer metastases than anti-EMA (Thor et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Cure rate in these patients is 50-60% (Berger et al, 1988); some of these patients have micrometastatic disease already at the time of the primary surgery (Berger et al, 1988;Fisher & Turnbull, 1955). Although in the absence of an adequate follow-up it is not possible to establish when the dynamic test has to be considered as 'true positive', i.e., leading to augmented antigen expression in those patients who will develop disease recurrence shortly after, two possibilities can be envisaged: either a shift from a negative (below the cut-off value) to a positive assay or a given increase of the antigen level irrespective of the basal value.…”
Section: Discussionmentioning
confidence: 99%
“…Diel et al [6] found a significant correlation between bone marrow positivity and tumor size (p < 0.001), nodal status (p = 0.001), histopathologic tumor grading (p = 0.002), and postmenopausal status of the study patients (p = 0.01). The London Ludwig Cancer Institute Group described that the presence of EMA-positive cells in bone marrow was significantly related to lymph node involvement, peritumoral vascular invasion, and size of the primary tumor [27]. Studies using different anticytokeratin monoclonal antibodies demonstrated merely a tendency towards correlation between detection of cytokeratin-positive cells in bone marrow and locoregional lymph node involvement antibodies [3,20,28].…”
Section: Introductionmentioning
confidence: 99%